Beware my spines: a new spiny fern (Dennstaedtia, Dennstaedtiaceae) from central and western Amazonia - Pena Nelson Túlio Lage; Zuquim Gabriela; Schwartsburd Pedro Bond (INST NACIONAL PESQUISAS AMAZONIA, 2022)
A new spiny fern belonging to the genus Dennstaedtia is described from Brazilian and Peruvian Amazonia. Dennstaedtia aculeata (sp. nov.) is the third spiny species known for the genus, and the first in South America. It is compared with another Neotropical spiny Dennstaedtia, D. spinosa. We also present images, illustrations and a distribution map of the specimens, and discuss the habitat preference of the species towards nutrient-richer soils and spinescence in the family.